Enrique Vila-Matas : juegos, ficciones, silencios - Oñoro, Cristina (Biblioteca filológica hispana ;, 2015)
This book offers a panoramic study of the narrative works and essays by Enrique Vila-Matas (Barcelona, 1948). The author identifies three key themes throughout his writings: games, fiction, and silence.